2005
DOI: 10.1681/asn.2004070556
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Role of Prostaglandin E2 EP4 Receptor in Furosemide-Induced Salt-Losing Tubulopathy

Abstract: Increased formation of prostaglandin E 2 (PGE 2 ) is a key part of hyperprostaglandin E syndrome/antenatal Bartter syndrome (HPS/aBS), a renal disease characterized by NaCl wasting, water loss, and hyperreninism. Inhibition of PGE 2 formation by cyclo-oxygenase inhibitors significantly lowers patient mortality and morbidity. However, the pathogenic role of PGE 2 in HPS/aBS awaits clarification. Chronic blockade of the Na-K-2Cl co-transporter NKCC2 by diuretics causes symptoms similar to HPS/aBS and provides a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 58 publications
1
39
1
1
Order By: Relevance
“…EP 2 and EP 4 receptor stimulation generally increases cAMP generation and signaling in the kidney. This would therefore be predicted to reduce sodium excretion and would apparently conflict with reports that EP 2 or EP 4 receptor blockade reduces sodium excretion [28,39]; however, a solution may be found in our recent studies. We showed that the cAMP-dependent pathway decreased the phosphorylation of two key regulator kinases that enhance ENaC activity, Akt and serum-and glucocorticoid-regulated kinase-1.…”
Section: Pharmacological Mechanisms Of Nsaids On Fluid and Blood Prescontrasting
confidence: 76%
See 2 more Smart Citations
“…EP 2 and EP 4 receptor stimulation generally increases cAMP generation and signaling in the kidney. This would therefore be predicted to reduce sodium excretion and would apparently conflict with reports that EP 2 or EP 4 receptor blockade reduces sodium excretion [28,39]; however, a solution may be found in our recent studies. We showed that the cAMP-dependent pathway decreased the phosphorylation of two key regulator kinases that enhance ENaC activity, Akt and serum-and glucocorticoid-regulated kinase-1.…”
Section: Pharmacological Mechanisms Of Nsaids On Fluid and Blood Prescontrasting
confidence: 76%
“…Chen et al [27] demonstrated that renal medullary EP 2 receptors participated in natriuresis in mice during a high-salt diet. Nüsing et al [28] generated a mouse model of HPS/aBS using prolonged administration of furosemide. They reported the involvement of EP 1 , EP 3 , and especially EP 4 receptor activation in the enhanced natriuresis in this model.…”
Section: Pharmacological Mechanisms Of Nsaids On Fluid and Blood Presmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of prostaglandin synthesis by NSAIDs and COX-2 inhibitors can result in fluid retention and other renal-based adverse effects, especially under certain disease conditions in which renal function becomes more dependent on prostaglandins (Curtis et al, 2004). Furosemide-induced natriuresis and diuresis represents a useful model for assessing the impact of PGE 2 suppression on sodium and fluid retention because of the increased renal dependence on COX-2-derived PGE 2 (Nü sing et al, 2005). EP receptors, notably EP4, have been shown to be important for furosemide-induced natriuresis in mice (Nü sing et al, 2005).…”
Section: Ep4 Antagonists For Chronic Arthritis 431mentioning
confidence: 99%
“…Furosemide-induced natriuresis and diuresis represents a useful model for assessing the impact of PGE 2 suppression on sodium and fluid retention because of the increased renal dependence on COX-2-derived PGE 2 (Nü sing et al, 2005). EP receptors, notably EP4, have been shown to be important for furosemide-induced natriuresis in mice (Nü sing et al, 2005). In agreement with this finding, we have demonstrated that antagonism of the receptor by MF498 results in significant antinatriuretic and antidiuretic effects similarly to the COX-2 inhibitor MF-tricyclic.…”
Section: Ep4 Antagonists For Chronic Arthritis 431mentioning
confidence: 99%